San Diego, California - 1913
Preparations for the International Exposition of Progress and Opportunity to be held in San Diego, California, throughout the entire year of 1915 have been underway for two years, and work on the buildings and grounds is now more than fifty per cent completed. The main group of fifteen exhibit buildings are to be of the California Mission style of architecture, and the grounds, containing six hundred and fifteen acres in Balboa Park, in the very heart of San Diego city, are being adorned with giant palms and all the varieties of tropical foliage and vegetation known to botanists. San Diego is the California Terminus of the Santa Fe Railway System. The State Societies of San Deigo send you this card on their Postcard Day, and hundreds of thousands of similar cards go to all parts of the world.